2021
DOI: 10.1002/cctc.202100204
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Synthesis of Ethanol via CO2 Hydrogenation over CoMoCx Catalysts

Abstract: Hydrogenation of CO 2 to ethanol is one of the promising and emerging routes for the transformation of CO 2 into value-added chemicals. In the present work, series of CoMoCx catalysts were prepared by using ionic liquids as all-in-one precursors and adjusted the proportional and electronic properties of CoMoC x catalysts by modifying carburization temperature, the efficiency of CO 2 to ethanol hydrogenation was optimized. Under the optimal reaction conditions (180°C and 2 MPa), the selectivity of ethanol reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…This step is also in accordance with several other studies. 512 The existence of alkali metal ions (M + ) could enhance the activity and stabilize the formyl intermediate by providing an electron-rich environment for the Cu center. Through the reductive elimination, Cu + −Cu + sites were regenerated, together with the continuous production of ethanol, methanol, or water.…”
Section: Catalyst Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This step is also in accordance with several other studies. 512 The existence of alkali metal ions (M + ) could enhance the activity and stabilize the formyl intermediate by providing an electron-rich environment for the Cu center. Through the reductive elimination, Cu + −Cu + sites were regenerated, together with the continuous production of ethanol, methanol, or water.…”
Section: Catalyst Developmentmentioning
confidence: 99%
“…Later in 2019, the Wang and Xiao group 517 further modified the catalyst with Ni, which accelerated the formation of CH x * and as a result enhanced the ethanol production (Table 18, entry 6). Regarding the use of Co, a CoMoC x catalyst was developed by Xiao, Wu and co-workers 512 in 2021 and showed 97.4% selectivity toward ethanol with its formation rate of 0.528 mmol g cat −1 h −1 at 180 °C. A recent breakthrough was made by Wang and co-workers 511 using a Cu supported on Zr 12 -MOF.…”
Section: Catalyst Developmentmentioning
confidence: 99%
“…Ethanol is another compound of interest that can be obtained through thermochemical CO 2 valorization (Reaction ). , In comparison with methanol and hydrocarbons, ethanol production is considered to occur almost exclusively through the intermediate RWGS reaction (Reaction ). ,, Combining reaction with the RWGS leads to the Reaction : , 2 normalC normalO + 4 normalH 2 normalC 2 normalH 5 normalO normalH + normalH 2 normalO goodbreak0em1em⁣ normalΔ H = prefix− 256 .25em normalk normalJ / normalm normalo normall 2 normalC normalO 2 + 6 normalH 2 normalC 2 normalH 5 normalO normalH + 3 normalH 2 normalO goodbreak0em1em⁣ normalΔ H = prefix− 73.6 .25em normalk normalJ / normalm normalo normall …”
Section: Thermochemical Reactionsmentioning
confidence: 99%
“…Although the RWGS reaction is endothermic, this positive enthalpy is outweighed by the negative enthalpy of the reaction converting CO into ethanol, thus making the global ethanol production process exothermic, favored by relatively low temperatures . It has been demonstrated by Kusama et al that ethanol yield could be maximized at temperatures between 240 and 260 °C …”
Section: Thermochemical Reactionsmentioning
confidence: 99%
“…Recent studies have shown that nonnoble and metal-based catalysts are investigated to provide highly efficient liquid phase ethanol from CO 2 hydrogenation. 39,69,71,[100][101][102][103][104][105][106] Direct CO 2 hydrogenation to ethanol is represented below: 107…”
Section: Co 2 To Ethanolmentioning
confidence: 99%